All the small things: How virus‐like particles and liposomes modulate allergic immune responses - Kratzer, Bernhard (Eur J Immunol, 2019)
Recent years have seen a dramatic increase in the range of applications of virus‐like nanoparticle (VNP)‐ and liposome‐based antigen delivery systems for the treatment of allergies. These platforms rely on a growing number of inert virus‐backbones or distinct lipid formulations and intend to engage the host's innate and/or adaptive immune system by virtue of their co‐delivered immunogens. Due to their particulate nature, VNP and liposomal preparations are also capable of breaking tolerance against endogenous cytokines, Igs, and their receptors, allowing for the facile induction of anti‐cytokine, anti‐IgE, or anti‐FcεR antibodies in the host. We here discuss the “pros and cons” of inducing such neutralizing autoantibodies. Moreover, we cover another major theme of the last years, i.e., the engineering of non‐anaphylactogenic particles and the elucidation of the parameters relevant for the specific trafficking and processing of such particles in vivo. Finally, we put the various technical advances in VNP‐ and liposome‐research into (pre‐)clinical context by referring and critically discussing the relevant studies performed to treat allergic diseases.